Characterizing the Flow and Interaction of Microbubbles in a 2D Capillary Network for Targeted Drug Delivery: A Simulation Study - Sadegh Shurche; Akram Shahidani; Roghaye Bodaghi Hossein Abadi (Frontiers in Biomedical Technologies)
Purpose: Microbubble ultrasound contrast agents inside the bloodstream enhance the ultrasound signals of the vascular bed. In addition, microbubbles can be used for treatment. The present study assesses how air bubbles flow in a microchannel 2D capillary network. The evaluated network mimics part of a capillary system by comprising multiple bifurcations.